Implementing a routine flow cytometry assay for nucleated red blood cell counts in cord blood units. (21st August 2016) - Simard, C.; Cloutier, M.; Jobin, C.; Dion, J.; Fournier, D.; Néron, S.
Summary: Introduction: As required by standards organizations, Héma‐Québec Cord Blood Bank performs enumeration of nucleated red blood cells (NRBCs) in cord blood units (CBUs). This study presents the validation and implementation approaches developed to transfer the routine NRBC enumeration from the manual blood film method to a flow cytometric assay. Methods: The flow cytometry method was adapted from Tsuji ( Cytometry, 37, 1999, 291). This assay was validated to assess the specificity, detection limit, repeatability, and reproducibility of the method, including interoperator and interlaboratory testing. Finally, postimplementation follow‐up and adjustments were performed for CBU over a 7‐month period. Results: Blood film and flow cytometry NRBC enumerations showed a strong correlation ( n = 40; Pearson's r correlation = 0.90). Validation was successful as exemplified by the correlation in interlaboratory testing ( n = 30; r = 0.98). During implementation, our routine laboratory analyses revealed that CBU with low NRBC content (≤2%), representing 26% of all CBU tested, resulted in 15% of repeated reading and/or staining and was the principal source of nonconformity. Small adjustments in the standard operating procedures (SOPs), including a fixed 200‐event setting in the NRBC gate for the second reading of the replicates, have completely solved this issue. Conclusion: Flow cytometric NRBC enumerations, now implemented in Héma‐Québec Public Cord Blood Bank, is an improvement in the efficiency of our operations by integrating the count for NRBC into our flow cytometry platform.